2020
DOI: 10.1016/j.redox.2020.101760
|View full text |Cite
|
Sign up to set email alerts
|

SOD1 suppresses pro-inflammatory immune responses by protecting against oxidative stress in colitis

Abstract: Superoxide dismutase 1 (SOD1) binds copper and zinc ions and is one of three superoxide dismutases responsible for destroying free superoxide radicals in the body. Reactive oxygen species (ROS), including free superoxide radicals, play important roles in colitis. However, the role of SOD1 in oxidative stress under colitis remains unclear. Here, we examined the role of SOD1 in the DSS-induced mouse model of colitis. SOD1 deficiency resulted in severe oxidative stress with body weight loss, epithelial barrier di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 50 publications
(32 reference statements)
3
52
0
Order By: Relevance
“…Under proinflammatory stimulus, the IKK complex can be activated by ROS produced by the GTP-binding protein Rac1 ( 116 ), leading to signal transduction pathways that contribute to TNF-α secretion. In line with this finding, ROS effects can be suppressed by SOD, reducing the pro-inflammatory immune responses by blocking the p38-MAPK/NF-κB signaling activation ( 117 ).…”
Section: Targets Of Ros In Macrophagesmentioning
confidence: 69%
“…Under proinflammatory stimulus, the IKK complex can be activated by ROS produced by the GTP-binding protein Rac1 ( 116 ), leading to signal transduction pathways that contribute to TNF-α secretion. In line with this finding, ROS effects can be suppressed by SOD, reducing the pro-inflammatory immune responses by blocking the p38-MAPK/NF-κB signaling activation ( 117 ).…”
Section: Targets Of Ros In Macrophagesmentioning
confidence: 69%
“…Here we suggest that an increase in SOD3 activity can improve the intestinal epithelial damage both in vitro and in vivo. Interestingly, a recent work has shown that SOD1 knockout mice exhibited increased susceptibility for DSS-induced colitis with upregulation of ROS and p38-MAPK signaling, in which oral administration of SOD could ameliorate the disease phenotype [ 39 ]. Considering the specific role and expression pattern of SOD isoforms in the intestine, it would be interesting to evaluate the therapeutic potential of SOD2- or SOD3 treatment in this model.…”
Section: Discussionmentioning
confidence: 99%
“…SOD1 binds copper and zinc ions and is one of three superoxide dismutases. SOD1 deficiency in the dextran-sodium sulphate (DSS)-induced mouse model of colitis resulted in severe oxidative stress with body weight loss, epithelial barrier disruption, and decreased antioxidant enzyme activities (9). In CD, lipid peroxidation was found to correlate positively with SOD1 (10).…”
Section: Discussionmentioning
confidence: 99%